Instructional proxemics and its impact on classroom teaching and learning / Cecilia Cheong Yin Mei, Heng Buai Chin and Fauziah Taib - Cheong Yin Mei, Cecilia; Buai Chin, Heng; Taib, Fauziah (Universiti Teknologi MARA Shah Alam, 2017)
Instructional proxemics refers to the use of space and spatial design in the instructional environment. This study aims at investigating the ways Chinese as Second Language (CSL) teachers use classroom physical space, body movement and positioning to convey interpersonal and pedagogical messages, and examine how such messages impact on classroom teaching and learning. Lessons conducted by four CSL teachers from the Selangor state were observed. Interview data gathered from both teachers and students were used to elicit information about teaching practices related to proxemics. Martinec's (2001) Engagement System was used to analyse the proxemics data. The present research findings indicate that the patterns of teachers' instructional proxemics in class are shaped by the existing classroom layout, students' seating arrangement, and the instructional activity of the day. The student-interview data also showed that students enjoyed having close interaction with their teachers. Therefore, teachers should vary their instructional activities and move around the class while teaching to ensure they have close social relations with their students. The findings also show that the sense of closeness between teacher and students enhance student learning.